Comparative effectiveness of three-dimensional scaffold, differentiation media and co-culture with native cardiomyocytes to trigger in vitro cardiogenic differentiation of menstrual blood and bone marrow stem cells. (July 2018) - Rahimi, Maryam; Zarnani, Amir-Hassan; Mobini, Sahba; Khorasani, Somaieh; Darzi, Maryam; Kazemnejad, Somaieh
Abstract: The main purpose of this study was to find effectiveness of 3D silk fibroin scaffold in comparison with co-culturing in presence of native cardiomyocytes on cardiac differentiation propensity of menstural blood(MenSCs)- versus bone marrow-derived stem-cells (BMSCs). We showed that both 3D fibroin scaffold and co-culture system supported efficient cardiomyogenic differentiation of MenSCs and BMSCs, as judged by the expression of cardiac-specific genes and proteins, Connexin-43, Connexin-40, alpha Actinin (ACTN-2), Tropomyosin1 (TPM1) and Cardiac Troponin T (TNNT2). No significant difference (except for higher expression of ACTN-2 in co-cultured MenSCs) was found between differentiation potential of the cells cultured in 3D fibroin scaffold and co-culture system. Collectively, our results imply that inductive signals served by biological factors of native cardiomyocytes to trigger cardiogenic differentiation of stem-cells may be efficiently provided by natural and biocompatible 3D fibroin scaffold suggesting the usefulness of this construct for cardiac tissue engineering.